The art of freedom : how artists see America - Raczka, Bob (Raczka, Bob. Bob Raczka's art adventures., 2008)
What is America? Shape a fascinating image of the United States through the eyes of eighteen artists who have painted, sculpted, and photographed the U.S. landscape and culture.